Real estate ownership and the demand for cars in Denmark: - A pseudo-panel analysis - Nielsen, Jens Erik (Proceedings from the Annual Transport Conference at Aalborg University, 2006)
This paper examines how real estate ownership, increasing real estate values and the falling interest rates affect car demand. It uses data from the Danish Transport Diary Survey together with data from Statistics Denmark to estimate a simple partial adjustment model for car availability in Danish households. We find that car availability differs among households owning real estate and households not owning real estate. Furthermore we show that both households groups have increased their demand for cars due to the falling interest rate.